2022
DOI: 10.29173/cjfy29787
|View full text |Cite
|
Sign up to set email alerts
|

No Young Carer Left Behind: A Two-Phased Study to Understand and Address the Needs of Young Carers from Rural and Urban Communities Before and During Covid-19

Abstract: Canada has one of the largest cohorts of young carers aged 15 to 24 who provide unpaid care for a family member. Although the body of research on young carers is growing in Canada, knowledge on the experiences and needs of young carers living in remote and rural communities is almost absent. This study aimed to understand and address the needs of young carers in rural/remote communities to support our community partner’s goal of expanding their resources and support of this underserved population. The study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…For example, caregiving responsibilities were reported to be unchanged (i.e., being homeschooled prior to the pandemic meant there was not a big disruption during the pandemic), decreased (i.e., due to less travel to appointments with pandemic lockdowns), and increased (i.e., household chores, meal preparation, mixing of school and caregiving time). This aligns with previous research highlighting the differences in lived experiences of young caregivers in the Canadian context as a non-homogenous group [13,15,21,40,[43][44][45].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For example, caregiving responsibilities were reported to be unchanged (i.e., being homeschooled prior to the pandemic meant there was not a big disruption during the pandemic), decreased (i.e., due to less travel to appointments with pandemic lockdowns), and increased (i.e., household chores, meal preparation, mixing of school and caregiving time). This aligns with previous research highlighting the differences in lived experiences of young caregivers in the Canadian context as a non-homogenous group [13,15,21,40,[43][44][45].…”
Section: Discussionsupporting
confidence: 90%
“…In total, 14 young caregivers joined the study. The social determinants of health [35,36] with intersectionality [37][38][39] guided the development of our interview guide alongside the lessons and findings we gleaned from a study we conducted on the experiences, challenges, and needs of young caregivers living in urban versus rural communities in Ontario, Canada [40]. Importantly, we acknowledge there is significant diversity in young caregiver populations and recognize this is not a homogeneous group.…”
Section: Methodsmentioning
confidence: 99%
“…Findings suggested that regional variations were significant in the availability of services, support, and experiences of young caregiver clients and their families during the COVID-19 pandemic. For example, access to the internet and the availability of programs and services were significant barriers for young caregivers and their families in rural communities, similar to the findings of a previous study [10] that compared young caregivers who lived in rural versus urban communities in the Canadian context (pre-pandemic).…”
Section: Discussionsupporting
confidence: 80%
“…Research on the lived experiences of young caregivers and their families in the Canadian context is growing [1,3,4,6,[9][10][11]; however, the available research does not report on the impact of the COVID-19 pandemic on young caregivers and their families in Canada. Even the study conducted by Newman and others (2022) [10], which collected data on young caregivers during the pandemic living in Ontario, Canada, did not capture the impact of the pandemic on young caregivers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation